2022
DOI: 10.1111/php.13710
|View full text |Cite
|
Sign up to set email alerts
|

One‐year Ocular Safety Observation of Workers and Estimations of Microorganism Inactivation Efficacy in the Room Irradiated with 222‐nm Far Ultraviolet‐C Lamps

Abstract: Two krypton‐chloride germicidal excimer lamp units (Care222 TRT‐104C11‐UI‐U3, USHIO Inc.) were installed in the examination room of an ophthalmology department. The irradiation dose was set not to exceed the former (i.e., before 2022) threshold limit value (TLV) (22 mJ cm−2/8 h) recommended by the ACGIH. Section 1: The eyes and lids of the six ophthalmologists (5 wore glasses for myopic correction) who worked in the room for a mean stay of 6.7 h week−1 were prospectively observed for 12 months. Slitlamp examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…The data of low UV irradiance (35 mW cm −2 ), which is commonly applied for airborne disinfection, was also included. 19,71,72 We found that for all UV irradiance, the endotoxin activity ratio linearly increased with the UV dose (R 2 = 0.74), supporting that the release of endotoxins was due to photochemistry (Fig. 3a).…”
Section: Effects Of Uv Dose Rh and Particle Phase Statessupporting
confidence: 58%
“…The data of low UV irradiance (35 mW cm −2 ), which is commonly applied for airborne disinfection, was also included. 19,71,72 We found that for all UV irradiance, the endotoxin activity ratio linearly increased with the UV dose (R 2 = 0.74), supporting that the release of endotoxins was due to photochemistry (Fig. 3a).…”
Section: Effects Of Uv Dose Rh and Particle Phase Statessupporting
confidence: 58%
“…Extensive studies in rat eyes by Kaidzu et al (17) concluded that the minimum far-UVC dose to induce corneal damage was far larger than the recommended regulatory limits (see below). A first in-situ study of human eye safety after long term far-UVC exposure was recently published (20), showing no adverse effects after 12-month exposures using multiple endpoints based on slit lamp examinations.…”
Section: Commentarymentioning
confidence: 99%
“…It has also been argued that the 10 mJcm -2 is incorrect due to the bandwidth of the monochromator used by Pitts in 1973 and the true threshold may be much higher than noted (20,23). In more recent work on Far-UVC, six ophthalmologists exposed to filtered 222 nm Far-UVC in their work environment for more than one year, demonstrated no ill eye effects (24).…”
Section: Introductionmentioning
confidence: 99%